Work Study Conflict and Work from Home in Enhancing Employee Motivation among Start-Up (Conceptual Paper) - Puji Nursyabani, Annisa; Silvianita, Anita (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this study is to determine the effect of work study conflict and work from home with role clarity on work motivation of start-up company employees. Data will be obtained from distributing questionnaires to 33 employees in 3 start-up companies in Indonesia who have outsourced employees who are also students. Then the data will be processed using SEM-PLS data analysis techniques using SmartPLS software. The findings in the literature show that there is a negative influence of work study conflict on work motivation, a positive influence of work from home on work motivation, and a positive influence of role clarity on work motivation